F02 A cluster of HD in italy with several subjects carrying cag expansion homozygousity in different generations and genetic risk over 50%. (September 2018) - Squitieri, Ferdinando; Dema, Maria Giovanna; Borrelli, Cristiana; Consoli, Federica; Luca, Alessandro De; Migliore, Simone
Abstract : Background: Huntington's disease (HD) prevalence is variable and depends on genetic background. However, culture, environment and other, yet unknown, biological factors may also play a role in determining its frequency. In Italy we estimate a prevalence of 11/100.000 (Squitieri et al., 2016). Methods: LIRH Foundation started to collect clinical and genealogical data together with DNA samples from patients and family members since 2001. Recently, we got in touch with a family from Calabria, Southern Italy, showing a high number of interrelationships and consequent increased risk of transmission of the mutation among people. Results: The family includes about 25 affected people with ascertained HD and hundreds at risk. However, there were two generations of people with homozygous CAG repeat expansion due to two intermarriages of mutation carrier people. The main kindred showed a homozygous mother married with a heterozygous father and 5 children whose four had an homozygous condition. They showed a different HD stage and were included into ENROLL-HD. These people had several 100% risk children. Conclusion: Nevertheless the large experience and the number of publications on genetic and psychological counseling in HD, the scientific community remains still unprepared on how to communicate such unusual risk of HD transmission. These conditions, moreover, contribute to an unpredictable frequency of the disease in some geographical areas.